Artificial urinary biomarker probes for diagnosis - Xu, Cheng (2024)
Urinalysis is a widely used medical test for healthcare monitoring and disease diagnosis. However, traditional urinalysis relies on endogenous biomarkers that have limited diagnostic sensitivity and specificity. To address these issues, molecular optical probes have been engineered to interact with disease biomarkers in vivo and produce artificial urinary biomarkers (AUBs). AUBs are then excreted into urine for the remote detection of diseases through urinalysis. In this Review, we first introduce AUB probes and highlight the benefits of AUBs over endogenous urinary biomarkers. We then discuss the design principles of two categories of these probes, namely, intrinsic AUB probes and AUB-secreting nanoprobes, with their corresponding detection modalities in urine test. Finally, we summarize the applications of AUB probes in disease diagnostics and discuss the current challenges and strategies to advance their clinical translation.